Correlation of soft tissue and skeletal injuries in cases of violent death: A retrospective study of autopsy cases for forensic anthropology. Issue 1 (11th November 2022) - Collini, Federica; Muccino, Enrico; Biehler‐Gomez, Lucie; Cummaudo, Marco; F. Gorio, Maria Carlotta; Cattaneo, Cristina
Abstract: In forensic pathology, deaths due to mechanical injuries (blunt, sharp, and gunshot) require an autopsy in order to determine the cause and manner of death through a detailed examination of viscera, soft tissues, and the skeletal system. Sometimes, such as in cases of severe putrefaction, only the skeleton is observable. In such cases, the absence of bony defects does not mean that a trauma‐related death should not be considered: yet, how often will a lethal mechanical death produce a defect in the skeletal system? The present study involved a retrospective review of autopsy reports to investigate the frequencies of soft tissue and related skeletal injuries in cases of violent deaths. A total of 200 autopsy reports for cases of four mechanisms of injury including sharp force trauma ( n = 50), gunshot ( n = 50), blunt force trauma ( n = 50), and mechanical asphyxia ( n = 50) were examined. Manner of death, localization of bone fractures, and correspondence between external injuries and bone fractures were reported. Frequencies of bone fractures and degree of correspondence with soft tissue injuries for each trauma group were evaluated. The result showed that lethal blunt trauma always caused bone fractures; 94.0% of violent deaths by gunshot involved bones; 48.0% of sharp force soft tissue injuries involved the bone tissue; and hyoid bone fractures were observed in 20.0% of cases of mechanical asphyxia.